Pendampingan Harga Pokok produksi, Pengembangan Dan Meningkatkan Pendapatan Umkm Kelurahan Kedung Sari Kec.Sukajadi Kota Pekanbaru (Studi Kasus Pada UMKM ABIERA) - Meesy Anugrah Putri; Nur Fitriana (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
MSMEs are a form of business that can provide many benefits and benefits to society. This service discusses the important role of assistance in managing production costs, development strategies, and efforts to increase the income of Micro, Small and Medium Enterprises (MSMEs). MSMEs play an influential role in the economy, but are often faced with various challenges, including efficient management of production costs, lack of knowledge about business development and MSME incomes that do not increase. In this context, comprehensive and sustainable assistance can provide the necessary support for MSMEs in managing and optimizing their production costs to be more competitive in an increasingly tight market. Apart from that, development strategy is also a crucial aspect in efforts to increase the competitiveness of MSMEs. With a well-planned development strategy, MSMEs can identify growth opportunities, develop new products or services, and expand their market reach. This will help MSMEs to develop sustainably and strengthen their position in the market. By increasing income, MSMEs can expand their businesses, improve the quality of products or services, and make a more significant contribution to the local and national economy. Through targeted assistance, implementing appropriate development strategies, and efforts to increase income, it is hoped that MSMEs can grow and develop sustainably, and be able to compete healthily in a dynamic and competitive market.